TARI KERAWUHAN DI BALI : SANGHYANG DEDARI SEBUAH KAJIAN SOSIAL - Nanik Sri Prihatini (Greget, 2000)
Dance kerawuhan (trance dance) is one of permorming art for the ritual event who stile a life in Bali. Sanghyang Dedari dance for its example, and used by Balinese society to ritual dance. Now that ritual art changed to be performance for tourisme.Key word: trance, wali, Sanghyang Dedari.